In both equations in the system, we know what y is equal to. Therefore, we can set the two equations equal to each other and solve for x.
-6(0.75)x = 4(x-1)
Simplify and distribute where needed.
-4.5x = 4x - 4
Combine like terms. We can subtract 4x to both sides to do so.
-8.5x = -4
Divide both sides by -8.5
x = 4/8.5 = 0.47059
Now plug x back into one of the equations and solve for y
4(0.47059 - 1) = -2.11765
So the answer is (0.47059, -2.11765)
This isn't one of the options so one of the equations may have been copied incorrectly. Hopefully this helps though!